Effectiveness of SARS-CoV-2 vaccination in patients with rheumatoid arthritis (RA) on DMARDs: as determined by antibody and T cell responses. Issue 1 (1st April 2022) - Saleem, Benazir; Ross, Rebecca L; Bissell, Lesley-Anne; Aslam, Aamir; Mankia, Kulveer; Duquenne, Laurence; Corsadden, Diane; Carter, Clive; Hughes, Pam; Nadat, Fatima A; Mulipa, Panji; Lobb, Mark; et al.
Abstract : Objectives: To assess antibody and T cell responses to SARS-CoV-2 vaccination in patients with rheumatoid arthritis (RA) on disease-modifying antirheumatic drugs (DMARDs). Methods: This prospective study recruited 100 patients with RA on a variety of DMARDs for antibody and T cell analysis, pre-vaccination and 4 weeks post-vaccination. Positive antibody response was defined as sera IgG binding to ≥1 antigen. Those that remained seronegative after first vaccination were retested 4 weeks after second vaccination; and if still seronegative after vaccination three. A T cell response was defined an ELISpot count of ≥7 interferon (IFN)γ-positive cells when exposed to spike antigens. Type I IFN activity was determined using the luminex multiplex assay IFN score. Results: After vaccine one, in patients without prior SARS-CoV-2 exposure, 37/83 (45%) developed vaccine-specific antibody responses, 44/83 (53%) vaccine-specific T cell responses and 64/83 (77%) developed either antibody or T cell responses. Reduced seroconversion was seen with abatacept, rituximab (RTX) and those on concomitant methotrexate (MTX) compared to 100% for healthy controls (p<0.001). Better seroconversion occurred with anti-tumour necrosis factor (TNF) versus RTX (p=0.012) and with age ≤50 (p=0.012). Pre-vaccine SARS-CoV-2 exposure was associated with higher quantitative seroconversion (≥3 antibodies) (p<0.001). In the subgroup of non-seroconverters, a second vaccination produced seroconversion in 54% (19/35), and after a third in 20% (2/10). IFN score analysis showed no change post-vaccine. Conclusion: Patients with RA on DMARDs have reduced vaccine responses, particularly on certain DMARDs, with improvement on subsequent vaccinations but with approximately 10% still seronegative after three doses.